Is the Funding of Public National Health Systems Sustainable over the Long Term? Evidence from Eight OECD Countries. (17th August 2016) - Angelis, Aris; Tordrup, David; Kanavos, Panos
Abstract: This study examines what impact macroeconomic and health‐related factors have on the financial sustainability of health care systems; provides insights on additional financial resources required in order for demand for health care to be met; and reflects on needed reforms by health care systems in the near future. Publicly available data are used to identify the key variables influencing health spending. Statistical analysis is used to provide estimates of future required levels of health spending. Average macroeconomic performance, high debt levels, the need to contain fiscal deficits combined with adverse demographic developments, high outlays on health technologies and competing public sector needs, suggest that a funding gap between required and committed levels of health spending will exist in the next few years. This funding shortfall can be significant and in cumulative terms may range between 39 per cent and 61 per cent of 2012 health expenditure levels over the 2013–2017 period. Health care decision makers will need to place emphasis on outcomes‐based reimbursement, set priorities based on efficiency rules, and implement organisational innovations in order to ensure affordability and sustainability. In the opposite case, contraction of services offered and exclusions from coverage are not unlikely. Abstract : Overall, in order for health care systems to remain financially sustainable over the long‐term and for publicly funded health care systems to retain their public nature, a number of incisive reforms need to be implemented.